Evaluation of The Lack Of Street Lighting: Case Study of Tonjong Roundabout - Fahmi Faizal Wahyudi; Indrastuti (LEADER: Civil Engineering and Architecture Journal, 2025)
Street lighting is installed along roads so people can see better at night. To increase road safety and lower accident rates, international organizations like the WHO have underlined the significance of adequate infrastructure, such as street lighting. As part of their efforts to reduce the number of traffic accidents across the country, the government and authorities are paying special attention to the lack of street lighting. The lighting conditions on the road connecting Jatiwangi with Majalengka city, specifically the Tonjong roundabout, still require maximum street lighting. Tonjong Roundabout is located in Majalengka Regency, which connects the Jatiwangi road section with the city of Majalengka. The questionnaire approach is the research methodology employed in this study. Crime rates and injuries from accidents increase due to a lack of street lighting, especially in developing countries, where investment in infrastructure is often limited. In some places, rapid urban growth is not matched by adequate infrastructure development, including sound lighting systems. A comprehensive evaluation of street lighting conditions at the local level will allow for implementing more targeted solutions that improve safety and comfort for all who use the roads. The study's findings indicated that street lighting had an average relevance rating of 1.34. Nonetheless, the average level of satisfaction with street illumination was 2.55; the difference between importance and satisfaction was -1.21. Up to 95% of respondents then anticipate that street lighting will be improved for increased driving safety.